Growth Response and Production of Soybean (Glyicine max (L.) on Application of Phosphorous Fertilizer and Rhizobium Inoculation - Dedy Susanto Manurung; Yaya Hasanah; Rosita Sipayung (Indonesian Journal of Agricultural Research, 2018)
Increased soybean production both from quantity and quality continues to be pursued with extensification and intensification. During this time, fertilization is one of the cultivation techniques that is expected to contribute significantly in increasing soybean production. This study aims to determine the response of growth and production of soybean to Phosphorous (P) fertilizer and rhizobium inoculation. This research was conducted at Jl. Deli Serdang Sumatera Utara, from August-November 2017 with P fertilizer (SP-36) treatments (0, 50, 100, 150 kg/ha) and Rhizobium inoculation treatments (0, 5, 10 g/kg of seed). Variables observed were number of nodule root, number of filled pods, dry weight of seed per plant, dry weight of seed per plot and dry weight of 100 seeds. The results showed rhizobium inoculation significantly affected to the number of effective root nodules (nodules), filled pods, dry weight of seed per plant and dry weight of seed per plot with the best treatment was Rhizobium inoculation 5g/kg of seed) while the P fertilizer treatment and interaction between the two had no significant effect to all variables observed.